Identification of ZOUPI Orthologs in Soybean Potentially Involved in Endosperm Breakdown and Embryogenic Development - Zhang, Yaohua (Front Plant Sci, 2017)
Soybean (Glycine max Merr.) is the world’s most widely grown legume and provides an important source of protein and oil. Improvement of seed quality requires deep insights into the genetic regulation of seed development. The endosperm serves as a temporary source of nutrients that are transported from maternal to filial tissues, and it also generates signals for proper embryo formation. Endosperm cell death is associated with the processes of nutrient transfer and embryo expansion. The bHLH domain transcription factor AtZHOUPI (AtZOU) plays a key role in both the lysis of the transient endosperm and the formation of embryo cuticle in Arabidopsis thaliana. There are two copies of soybean GmZOU (GmZOU-1 and GmZOU-2), which fall into the same phylogenetic clade as AtZOU. These two copies share the same transcription orientation and are the result of tandem duplication. The expression of GmZOUs is limited to the endosperm, where it peaks during the heart embryo stage. When the exogenous GmZOU-1 and GmZOU-2 were expressed in the zou-4 mutant of Arabidopsis, only GmZOU-1 partially complemented the zou mutant phenotype, as indicated by endosperm breakdown and embryo cuticle formation in the transgenic lines. This research confirmed that the GmZOU-1 is a ZOU ortholog that may be responsible for endosperm breakdown and embryo cuticle formation in soybean.